Jog Your Mind: methodology and challenges of conducting evaluative research in partnership with community organizations. (17th July 2014) - Bier, Nathalie; Lorthios-Guilledroit, Agathe; Nour, Kareen; Parisien, Manon; Ellemberg, Dave; Laforest, Sophie
ABSTRACT: Background: Jog Your Mind is a community-based program aiming at empowering elderly people to maintain their cognitive abilities using a multi-strategic approach including cognitively stimulating activities, mnemonic strategies, and strategies to promote healthy behaviors. It is offered to elderly individuals without known or diagnosed cognitive impairment by volunteers or community practitioners over ten weekly sessions. This paper describes the protocol of a quasi-experimental study designed to evaluate Jog Your Mind . Methods: Community responsible to recruit participants were either assigned to the experimental group (participating in the Jog Your Mind program) or to the control group (one-year waiting list). All participants were interviewed at baseline (T1), after the program (T2), and 12 months after the baseline (T3). Primary outcomes were the use of everyday memory strategies and aids and subjective memory functioning in daily life. Secondary outcomes included attitudes, knowledge, and behaviors related to cognitive vitality and cognitive abilities (memory and executive functions). Program delivery, organizational and environmental variables were recorded to document the implementation process. Results: Twenty-three community organizations recruited 294 community-dwelling elderly individuals in total at T1. Between T1 and T3, an attrition rate of 15.2% was obtained. Conclusions: Jog Your Mind is one of the only programs targeting cognition among older adults being offered in community settings by community practitioners. The protocol described was designed with a focus on maximizing broad generalizations of the results while achieving scientific rigor. It can serve as an example to guide future research aiming to evaluate health interventions under natural conditions.